The Circumstances of the Publication of Christian Gottlieb Mielcke’s Collection of Sermons Mißknygos: Evidence from Archival Documents - Sidabraitė, Žavinta (Senoji Lietuvos literatūra, 2024)
Mißknygos (Königsberg 1800), a collection of sermons prepared by Christian Gottlieb Mielcke (Lith. Kristijonas Gotlybas Milkus, 1733–1807), was a translation of Johann Gottlob Heim’s (1738–1788) postil for peasants Vollständige Sammlung von Predigten für christliche Landleute über alle Sonn- und Festtagsevangelia des ganzen Jahres (Züllichau & Frezstadt 1796); it was slightly shortened and supplemented with two original sermons. The research presented in this article is based on documents stored in the Secret State Archive Prussian Cultural Heritage Foundation (Geheimes Staatsarchiv Preußischer Kurlturbesitz, GStA PK): (1) a request from the printers Gottlieb Lebrecht Heering (?–1808) and George Karl Haberland (?–1835) to the East Prussian government in Königsberg to ensure the distribution of a certain number of Mißknygos in schools and churches of Prussian Lithuania (Königsberg, 9 February1799); (2) a letter from Daniel Friedrich Mielcke (Lith. Danielius Frydrichas Milkus, 1738–1818), chief pastor and inspector of schools in Ragnit (Lith. Ragainė), to Christoph Friedrich Heilsberg (1725–1807), an assessor at the Chamber for War and Domains (Kriegs- und Domänenkammer), regarding various official matters (Ragnit, 11 April 1799); (3) a letter from Christian Gottlieb Mielcke, the cantor of the Pillkallen (Lith. Pilkalnis), to Christoph Friedrich Heilsberg on vocabulary, grammar, the postil, and other matters (Pillkallen, 11 April 1799); (4) a letter from Daniel Friedrich Mielcke to the Ministry of the Eastern Province in Königsberg concerning the distribution of Mißknygos (Ragnit, 28 September 1800). Archival sources reveal that Mielcke’s initiative to publish a collection of Lithuanian sermons for peasants was supported by Christoph Friedrich Heilsberg, who came from Ragnit and was an assessor of the Chamber for War and Domains and a school assessor. His authority was invoked by the printers Heering and Haberland in their request to guarantee the distribution, at the expense of schools and churches, of a certain number of copies of the postil to be printed. Letters from Christian Gottlieb and his brother Daniel Friedrich Mielcke make it clear that a little over a year had been spent on the work on the postil and that translations of the sermons were sent to the publishers in parts. Christian Gottlieb Mielcke’s work on the sermons was interrupted in early 1799 by the idea to prepare and publish the grammar Anfangs-Gründe einer Littauischen Sprach-Lehre together with the dictionary Littauisch-deutsches und Deutsch-littauisches Wörter-Buch and to write a preface for this publication (the composite volume was printed in 1800). At that time, Christian Gottlieb Mielcke asked Heilsberg to mediate, so that the printers would give him a break in the translation of the sermons. Daniel Friedrich Mielcke’s letter shows that in April of the same year, Christian Gottlieb asked for his brother’s assistance and received his consent to help him. It is quite likely that at the same time Christian Gottlieb Mielcke asked Ephraim Friedrich Meissner (1731–1815), the pastor of Schirwindt (Lith. Širvinta), to help him. (In addition to Christian Gottlieb Mielcke’s own translations, the collection of sermons contains four sermons by Daniel Friedrich Mielcke as well as two original sermons and ten translated sermons by Efraim Friedrich Meissner.) The negative resolution of Friedrich Gottfried von der Groeben (1726–1799), a real privy councillor (Wirklicher Geheimer Rat) and a minister, in a letter from Heering and Haberland shows that their request for the distribution of Mißknygos at the expense of the schools and the church was not granted. Still, the publishers resolved to release the collection. Daniel Friedrich Mielcke’s letter of 28 September 1800 shows that the Mißknygos were published in late summer or early autumn of that year. Now it was Daniel Friedrich Mielcke who in his letter asked the churches of Prussian Lithuania to be allowed to acquire one copy of the book each. Christoph Albrecht von Ostau (1735–1805), who had succeeded von Groeben as the real privy counsellor and minister, granted Mielcke’s request and instructed the churches in the region to purchase the book from their own funds. Ostau’s decree explained the relatively quick distribution of Mißknygos, which brought profits to Heering and Haberland’s printing house and confirmed the efficiency of the usual scheme of distributing Lithuanian religious publications through churches and schools.